(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article provides information about pedagogy, a brief history of the word. There is also information about innovative pedagogy, with specific facts about the importance of this concept. Adequacy of the level of knowledge about a person’s mental development and upbringing is the only requirement of objectivity. It should be noted that wellknown names are also given about humanism